2016
DOI: 10.1186/s10194-016-0601-5
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of a behavioural intervention for migraine headache: a qualitative study

Abstract: BackgroundMigraine headache has a high prevalence and a severe impact on personal, social and work life, forming a significant burden on patients, service providers and society. There is some evidence of the effectiveness of behavioural interventions to supplement drug therapy but a recognised need to identify an effective minimal contact approach to enhance access and provide a model for use in publicly funded health systems. This study uses in-depth interviews to examine patients’ experience and responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 27 publications
1
35
0
2
Order By: Relevance
“…The study of minimal-contact CBT + RT reported that participants found the relaxation aspects of therapy easier to implement. CBT components of therapy were more challenging to learn and apply in the context of a minimal-contact intervention [44]. Improvements in headache seen in this review in studies using CBT related interventions are less than those reported by Goslin et al [10].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The study of minimal-contact CBT + RT reported that participants found the relaxation aspects of therapy easier to implement. CBT components of therapy were more challenging to learn and apply in the context of a minimal-contact intervention [44]. Improvements in headache seen in this review in studies using CBT related interventions are less than those reported by Goslin et al [10].…”
Section: Discussionmentioning
confidence: 98%
“…These low intensity interventions demonstrated a modest efficacy in migraine reduction, which is of particular relevance because, such approaches are likely to be less costly, hence, potentially more cost-effective [43]. A recent paper provides some understanding of patients’ views using qualitative methods, with interviews [9, 44]. Combining trial methodology with qualitative methods is recommended by the Medical Research Council, but so far not used in trials of psychological interventions for migraine [45].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, chronic headache sufferers face a dilemma in social relationships, about concealing or make evident their disease: if patients conceal their condition they risk carrying the burden of the disease alone, with no social support; on the other hand, making chronic headache visible could result in stigma . Morgan and colleagues underlined that the qualitative method was particularly appropriate to investigate the feelings of the patients with migraine and their expectations toward the therapy, highlighting the importance of a patient‐centered approach to create tailored programs . The meaning of living with migraine was also investigated in a qualitative study by Rutberg and Öhrling.…”
Section: Introductionmentioning
confidence: 99%
“…Data were sparse regarding descriptions of the participants. Only 1 of the 10 reviewed studies reported race of participants, which was mostly white . Few studies appeared to capture data based on the HA treatment clinical practice guidelines.…”
Section: Resultsmentioning
confidence: 99%